From compound and dispense to compound, print and dispense - the coming of the 3D drug printing / Prof. Dato' Dr. Abu Bakar Abdul Majeed - Abdul Majeed, Abu Bakar (Faculty of Pharmacy, 2023)
A possible scenario in the near future - you have a prescription from the doctor which you receive via your smartphone. You then take it to a pharmacy where you will have your medications compounded, 3D printed and dispensed by the pharmacist, just like a print-on-demand service, currently offered for clothing and housewares. You may choose the colour, shape and size of your tablets, and perhaps to have several medications embedded within one single tablet so that it is convenient for you to swallow just one, instead of the usual handful of tablets. For refills, you simply return to the pharmacy and have them printed. Forget about the queue at the hospital. Even better, if you have enough funds, procure a drug 3D printer and print the medications at home. Then, simply e-consult the pharmacist on the proper use of the medication.